Transaxillary Thoracodorsal Artery Perforator Flap: A Versatile New Technique for Hypopharyngeal Reconstruction - Amin, Ayman Abdel-Wahab; Rifaat, Mohammed; Ellabban, Mohamed Ahmed; Zedan, Mohamed; Kamel, Mohamed; Bassiouny, Mahmoud (Journal of Reconstructive Microsurgery, 2014)
Introduction Reconstruction of the hypopharynx and cervical esophagus after tumor resection remains a challenging problem. Different techniques of reconstruction have been described for such defects. Although free flap reconstruction, including jejunum and fasciocutaneous flaps, has gained popularity for this complex defect, regional flaps are still in use worldwide.Patients and Methods We present our experience using the pedicled thoracodorsal artery perforator (TDAP) flap whereby only a small cuff of latissimus dorsi muscle around the perforators is harvested. The remaining muscle with its nerve supply is preserved. The flap is delivered to the neck through the cervicoaxillary tunnel. It was used as a complete tube in six patients and with an additional attached skin island for reconstruction of the neck skin in another four patients.Results A total of 11 TDAP flaps were used for reconstruction in 10 patients. All flaps survived except in one patient who suffered from a complete flap loss. This was salvaged by another TDAP flap from the contralateral side. Partial sloughing of the outer part of the pedicled TDAP occurred in one other patient. Pharyngeal fistulas developed in another two patients and eventually healed spontaneously. All patients resumed an oral diet within 2 weeks except two with fistulas. All patients resumed their shoulder active range of motion within 3 weeks.Conclusion The transaxillary TDAP flap is an ideal technique for hypopharyngeal reconstruction. It offers the advantages of free fasciocutaneous flaps, has a wide arc of rotation, a relatively larger flap dimension, a reliable vascular pedicle, and acceptable donor site morbidity.
Keywords: thoracodorsal artery flap; hypopharynx; transaxillary